2002
DOI: 10.1002/ijc.10469
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional anti‐angiogenic activity of the cyclic peroxide ano‐2 with antitumor activity

Abstract: Our focus was to develop an anti-angiogenic drug possessing the inhibitory activity of urokinase-type plasminogen activator (u-PA) production. During preliminary screening, the effects of 13 ozonides on the inhibition of u-PA production in human fibrosarcoma HT-1080 cells and on the inhibition of angiogenesis on chicken embryonic chorioallantoic membranes were determined. Of the ozonides tested, 9 inhibited in vitro u-PA production of HT-1080 cells and 7 of these 9 exhibited strong anti-angiogenic activity. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…These compounds probably generate oxygen reactive species (ROS) that cause apoptosis by induced oxidative stress. 57 Arakawa et al 58 reported that ozonide (cyclic peroxide) exhibits multiantiangiogenic and potent antitumor activity in vitro and in vivo against human fibrosarcoma HT-1080 cells. However, no data were found regarding the antitumor properties of ozonated oils.…”
Section: Cytotoxicity and Antitumor Activitymentioning
confidence: 99%
“…These compounds probably generate oxygen reactive species (ROS) that cause apoptosis by induced oxidative stress. 57 Arakawa et al 58 reported that ozonide (cyclic peroxide) exhibits multiantiangiogenic and potent antitumor activity in vitro and in vivo against human fibrosarcoma HT-1080 cells. However, no data were found regarding the antitumor properties of ozonated oils.…”
Section: Cytotoxicity and Antitumor Activitymentioning
confidence: 99%
“…This implies to us that microbial metabolites could provide an appealing treasury of effective angiogenesis inhibitors, (12) although compounds that are not derived from microorganisms might show antiangiogenic activity. (13)(14)(15)(16)(17)(18)(19)(20)(21)(22) In fact several research groups, including ours, have shown that a number of seemingly unrelated classes of small molecules derived from microorganisms interfere with angiogenesis in in vitro and in vivo experimental models. (23)(24)(25)(26)(27) Our microbial inhibitors of angiogenesis include herbimycin, eponemycin, cytogenin and rhizoxin.…”
mentioning
confidence: 99%